2017
DOI: 10.1073/pnas.1704173114
|View full text |Cite
|
Sign up to set email alerts
|

BMTP-11 is active in preclinical models of human osteosarcoma and a candidate targeted drug for clinical translation

Abstract: Osteosarcoma occurs predominantly in children and young adults. High-grade tumors require multidisciplinary treatment consisting of chemotherapy in the neoadjuvant and adjuvant settings, along with surgical intervention. Despite this approach, death from respiratory failure secondary to the development and progression of pulmonary metastases remains a significant problem. Here, we identify the IL-11 receptor α subunit (IL-11Rα) as a cell surface marker of tumor progression that correlates with poor prognosis i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…Bone metastasis-targeting peptidomimetic (BMTP-11) directed against IL-11Rα retards primary tumor growth and lung metastasis in preclinical models of human osteosarcoma. BMTP-11 in combination with gemcitabine shows better outcomes than BMTP-11 alone [59]. Similarly, targeting IL-11Rα in combination with doxorubicin therapeutically improves the effect of chemotherapy in high grade Type I endometrioid cancer [60].…”
Section: Identification Of Il-6 Family Cytokines As Potential Cancmentioning
confidence: 99%
“…Bone metastasis-targeting peptidomimetic (BMTP-11) directed against IL-11Rα retards primary tumor growth and lung metastasis in preclinical models of human osteosarcoma. BMTP-11 in combination with gemcitabine shows better outcomes than BMTP-11 alone [59]. Similarly, targeting IL-11Rα in combination with doxorubicin therapeutically improves the effect of chemotherapy in high grade Type I endometrioid cancer [60].…”
Section: Identification Of Il-6 Family Cytokines As Potential Cancmentioning
confidence: 99%
“…Osteosarcoma is a common malignant bone tumor in children and young adults with a high rate of recurrence and a strong tendency to metastasize to distant organs such as the lungs 1 - 3 . Current treatment options for osteosarcoma mainly include neoadjuvant chemotherapy, tumor amputation and postoperative chemotherapy, which enhance the survival rate of patients with osteosarcoma 1 - 3 . Nevertheless, death from respiratory failure due to lung metastases remains a significant problem 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment options for osteosarcoma mainly include neoadjuvant chemotherapy, tumor amputation and postoperative chemotherapy, which enhance the survival rate of patients with osteosarcoma 1 - 3 . Nevertheless, death from respiratory failure due to lung metastases remains a significant problem 1 . Moreover, the use of chemotherapeutic agents (cisplatin, doxorubicin, methotrexate, etc. )…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, IL11Ra expression has been demonstrated in lung metastasis from OS patients, whereas almost no, or poor expression was observed in healthy surrounding tissues . Recently, a correlation between cancer progression and IL‐11Ra activity was demonstrated using patient biopsies and metastatic versus non‐metastatic cell lines . This suggests that IL11Ra could be essential for tumour development.…”
Section: Il‐11ramentioning
confidence: 99%
“…The novelty in the targeting of IL‐11Ra resides in the strategy that was used to discover it: A combinatorial phage library was screened, and a cyclic nonapeptide was isolated and shown to specifically and selectively bind to the receptor . This peptide was then synthesized in tandem to a peptidomimetic motif previously shown to trigger cell death by mitochondrial membrane disruption has followed its preclinical development with the name BMTP‐11 for OS and other cancer types . A few years after its isolation, Huang and colleagues combined this peptide to a CAR scaffold construct (Figure ) and showed that it had the ability to redirected T cells towards OS .…”
Section: Il‐11ramentioning
confidence: 99%